Kenya Groundwater Governance Case Study - Mumma, Albert (World Bank, Washington, DC, 2014)
This report presents a case study on groundwater governance in Kenya. The objectives of the study were to: (a) describe groundwater resource and socioeconomic settings for four selected aquifers; (b) describe governance arrangements for groundwater management in Kenya; and (c) identify the relevance of these arrangements for planning and implementing climate change mitigation measures. The report provides a comprehensive strategy to develop effective groundwater management and a pilot groundwater management plan. Kenya's draft Policy for the Protection of Groundwater provides most of the requirements for improving groundwater governance, including participation and empowerment of groundwater users, decentralization of management to local level, integration of surface and groundwater management, improving monitoring and data collection, identifying sites for managed aquifer recharge (MAR), mapping strategic aquifers and conjunctive use opportunities, and identifying groundwater conservation areas. Groundwater management decision making is sector-based and on the whole ad hoc; there is no mechanism for coordination and for fostering cross-sector linkages. Consequently, the management of groundwater resources has continued to be carried on in isolation from the management of land and other land-based resources, with the inevitable consequence that the implications of management decisions in critical areas such as physical are planning, land use planning, and agricultural activities have often been overlooked. At the same time, groundwater decision making remains overly centralized, with limited real involvement of stakeholder units, such as catchment area advisory committees (CAACs) and water resources user associations (WRUAs).